2019
DOI: 10.1021/acssuschemeng.8b06822
|View full text |Cite
|
Sign up to set email alerts
|

Novel Deep Eutectic Solvents for Highly Efficient and Reversible Absorption of SO2 by Preorganization Strategy

Abstract: Deep eutectic solvents (DESs) have emerged as promising substitutes for SO2 capture. In this work, an effective preorganization strategy was implemented to design DESs, aiming at improving the SO2 desorption property while ensuring the SO2 absorption capacity in DESs. Several novel DESs with the preorganized multi-imides as hydrogen bond donors were synthesized and evaluated for SO2 capture. The results showed that the studied DESs exhibited high SO2 absorption capacities. In particular, the ethylenurea (EU)/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…Comparing the FTIR spectra before and after absorption of SO 2 , new absorption peaks at 542, 645, 947, 1046, 1283, and 1390 cm −1 for both [TMEA][Im] and TMEA were found. Among these new peaks at 1390, 1046, and 542 cm −1 belong to the symmetric stretching vibration, symmetric stretching vibration, and bending vibration of S═O, 23,56,57 respectively. This phenomenon is mainly attributed to the physical interaction between ether oxygen atom and SO 2 54 .…”
Section: Resultsmentioning
confidence: 96%
“…Comparing the FTIR spectra before and after absorption of SO 2 , new absorption peaks at 542, 645, 947, 1046, 1283, and 1390 cm −1 for both [TMEA][Im] and TMEA were found. Among these new peaks at 1390, 1046, and 542 cm −1 belong to the symmetric stretching vibration, symmetric stretching vibration, and bending vibration of S═O, 23,56,57 respectively. This phenomenon is mainly attributed to the physical interaction between ether oxygen atom and SO 2 54 .…”
Section: Resultsmentioning
confidence: 96%
“…With the optimal molar ratio, the absorption capacities of EmimCl:EG DES (1:2) and EmimCl:TEG DES (1:4) were 1.03 and 1.20 g SO 2 /g DES, respectively, at 293. 15 The effect of HBAs and HBDs in DESs was further investigated by Tantai et al [44]. As shown in Figure 2, the gravimetric SO 2 absorption capacities of ethylenurea (EU) and 1,3dimethylurea (DMU)-based DESs with various HBAs displayed the same trend: EmimCl > BmimCl > BmimBr > TBAC~P 4444 Cl.…”
Section: Imidazolium-based Dessmentioning
confidence: 92%
“…Moreover, it was also noted that when the SO 2 partial pressure decreased to 2 kPa at 298. 15 [44]. Copyright (2019) American Chemical Society).…”
Section: Imidazolium-based Dessmentioning
confidence: 99%
“…The preparation of all studied DESs in this work was similar to the reported method . All DESs with certain molar ratios were synthesized through simply mixing BmimCl (HBA), EU (primary HBD), and azole derivatives (secondary HBDs) together with stirring and heating under a nitrogen atmosphere, denoted as EU/azole derivatives/BmimCl ( a / b / c ), where a / b / c is the molar ratio of HBDs and HBA.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous reports, , though it has been proved that adjusting the HBD/HBA proportion and decreasing the basicity of HBDs or HBAs could significantly tune the interaction between DESs and SO 2 , it could also inevitably reduce the SO 2 absorption capacity. Previously, we reported that the DESs with the preorganized multi-imide ethylene urea (EU) such as HBD presented superior SO 2 absorption capacity, improved desorption performance, and outstanding physical properties . However, on the basis of the spectroscopic investigations and quantum chemical calculations, it could be concluded that the EU-based DESs interacted with SO 2 only through physical interactions, which resulted in the inferior SO 2 absorption capacity at low concentration.…”
Section: Introductionmentioning
confidence: 99%